How Does Collectivism Affect Social Interactions? A Test of Two Competing Accounts. (March 2021) - Liu, Shi S.; Shteynberg, Garriy; Morris, Michael W.; Yang, Qian; Galinsky, Adam D.
How does the cultural construct of collectivism impact social interactions? Two accounts of collectivism offer diverging predictions. The collectivism-as-values account proposes that people in collectivistic cultures prioritize their ingroup relationships; accordingly, this account predicts that collectivistic cultures will have more harmonious ingroup interactions than individualistic cultures. The socioecological account holds that individualistic cultures have high relational mobility, which requires people to invest in their ingroup relationships, whereas collectivistic cultures feature more fixed relationships that do not require positive engagement. To test these competing hypotheses about ingroup relationships across cultures, we sampled the daily interactions of college students in China and the United States. Results revealed that the individualistic culture (United States) had more positive ingroup interactions, more gratitude, and more emotional support than the collectivistic culture (China). The current findings are consistent with the socioecological account of collectivism and the effects of relational mobility on social relationships.